Numerical simulation of pararotor dynamics: Effect of mass displacement from blade plane - Piechocki, Joaquín (2016)
The pararotor is a biology-inspired decelerator device based on the autorotation of a rotary wing, whose main purpose is to guide a load descent into a certain planetary atmosphere. This paper focuses on a practical approach to the general dynamic stability of a pararotor whose center of mass is displaced from the blade plane. The numerical simulation tool developed is based upon the motion equations of pararotor flight, utilizing a number of simplifying hypotheses that allow the most influencing factors on flight behavior to be determined. Several simulated cases are analyzed to study the effect of different parameters associated with the pararotor configuration on flight dynamics, particularly the center of mass displacement from the blade plane. It was confirmed that the ability to reach stability conditions depends mainly on a limited number of parameters associated with the pararotor configuration: the relationship between principal moments of inertia, the planform shape (associated with blade aerodynamic coefficients and blade area) and the vertical distance between the center of mass and the blade plane. As a result different types of equilibrium solutions are found and the effect of each parameter is characterized. A bifurcation in the stability shape to a precessing conical rotation, not previously found in the linear stability analysis, is predicted by this numerical model.